Hubungan Pelaksanaan Discharge Planning Terstruktur Dengan Kepatuhan Kontrol Ulang Pasien Rawat Inap Di Rumah Sakit Natar Medika - greita andriana; Elasari, Yunina; Setiawan, Moh Heri; Wulandari, Rizki Yeni (LPPM Universitas Sari Mulia, 2025)
Background: One of the qualities of health services is post-inpatient patient compliance with control examinations after undergoing in-patient treatment at the hospital. Factors that can cause compliance to return control are the provision of discharge planning. Discharge planning has an important influence on health services, including reducing the occurrence of rehospitalization. Meanwhile, the current phenomenon is that the implementation of discharge planning at Natar Medika Hospital is still not good, this can be proven from the results of the pre-survey, 5 out of 10 patients stated that discharge planning was not implemented. by nurses properly. Purpose: This study was to determine the relationship between the implementation of discharge planning and compliance with re-control of post-inpatient patients at Natar Medika Hospital. Method: This research uses the Analytical Survey method with a cross sectional approach. The sample in this study amounted to 94 respondents using proportionate stratified random sampling technique. This research was carried out from July 22 to September 7 2024. Results: The research that was carried out found that 85 (90.5%) respondents were in the good category in implementing discharge planning. Meanwhile, 88 (93.6%) respondents underwent re-control after hospitalization. The statistical test results obtained p-value = 0.002, which means p<α = 0.005. Conclusion: There is a relationship between the implementation of structured discharge planning and patient compliance with post-hospitalization follow-up. It is hoped that the results of this research can increase nurses' motivation in implementing discharge planning better, so that patients do not experience rehospitalization before it is time for control patients.